2021
DOI: 10.4314/bcse.v34i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of Eremomastax speciosa (Hochst.) Cufod leaves and its cytotoxic potential on NIH-3T3 cells

Abstract: This study aimed at assessing the cytotoxicity of Eremomastax speciosa crude extract on NIH-3T3 fibroblast cell lines and reporting the chemical constituents in the extract. The MTT assay on NIH-3T3 cells showed a significantly lower (p < 0.05) inhibition from E. speciosa (IC50 > 30 µg/mL) compared to cyclohexamide (IC50 > 0.8 µg/mL). This result validates the non-toxicity observed with the use of E. speciosa on normal cells at low to moderate doses. Four compounds were isolated and identified from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Many fatty acids were identified in the topical cream. GC-MS is suitable for the identification of volatile and fatty components of natural extracts and plant samples including fatty acids (Eve et al, 2020;Carol et al, 2017;Koudoro et al, 2022). It could be suggested that most of the fatty acids are coming from the beeswax and shea butter which were used as important matrix components for the production of the cream.…”
Section: Discussionmentioning
confidence: 99%
“…Many fatty acids were identified in the topical cream. GC-MS is suitable for the identification of volatile and fatty components of natural extracts and plant samples including fatty acids (Eve et al, 2020;Carol et al, 2017;Koudoro et al, 2022). It could be suggested that most of the fatty acids are coming from the beeswax and shea butter which were used as important matrix components for the production of the cream.…”
Section: Discussionmentioning
confidence: 99%